2013
DOI: 10.1007/s10735-013-9537-0
|View full text |Cite
|
Sign up to set email alerts
|

A novel adenoviral vector-mediated mouse model of Charcot-Marie-Tooth type 2D (CMT2D)

Abstract: Charcot-Marie-Tooth disease type 2D is a hereditary axonal and glycyl-tRNA synthetase (GARS)-associated neuropathy that is caused by a mutation in GARS. Here, we report a novel GARS-associated mouse neuropathy model using an adenoviral vector system that contains a neuronal-specific promoter. In this model, we found that wild-type GARS is distributed to peripheral axons, dorsal root ganglion (DRG) cell bodies, central axon terminals, and motor neuron cell bodies. In contrast, GARS containing a G240R mutation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…In previous studies, ATF3 activation by injurious stimuli was associated with deterioration of motor neurons (Tsujino et al 2000;Hai & Hartman 2001;Vlug et al 2005;de Waard et al 2010) and with cell death programs (Hai & Hartman 2001;Nakagomi et al 2003;Raivich et al 2004). In this animal model, ATF3 expression was increased in L129P mutant hGARS-expressing motor neurons compared with WT hGARS-expressing neurons; in addition, the regions near motor neurons in the L129P-expressing ventral horn were surrounded by more Iba1-positive microglial cells compared with the WT-expressing ventral horn (Seo et al 2014c). These results indicate that in dSMA-V, the expression of L129P mutant hGARS induces ATF3 activation in ventral motor neurons, and ATF3 activation triggers motor cell death programs through neuroinflammation mediated by microglia, similarly to the effects on ATF3 and microglia in ALS (Vlug et al 2005;Beers et al 2006;Boillée et al 2006;Yamanaka et al 2008).…”
Section: Adenoviral Vector-mediated Animal Models For Motor Impairmentsupporting
confidence: 47%
See 4 more Smart Citations
“…In previous studies, ATF3 activation by injurious stimuli was associated with deterioration of motor neurons (Tsujino et al 2000;Hai & Hartman 2001;Vlug et al 2005;de Waard et al 2010) and with cell death programs (Hai & Hartman 2001;Nakagomi et al 2003;Raivich et al 2004). In this animal model, ATF3 expression was increased in L129P mutant hGARS-expressing motor neurons compared with WT hGARS-expressing neurons; in addition, the regions near motor neurons in the L129P-expressing ventral horn were surrounded by more Iba1-positive microglial cells compared with the WT-expressing ventral horn (Seo et al 2014c). These results indicate that in dSMA-V, the expression of L129P mutant hGARS induces ATF3 activation in ventral motor neurons, and ATF3 activation triggers motor cell death programs through neuroinflammation mediated by microglia, similarly to the effects on ATF3 and microglia in ALS (Vlug et al 2005;Beers et al 2006;Boillée et al 2006;Yamanaka et al 2008).…”
Section: Adenoviral Vector-mediated Animal Models For Motor Impairmentsupporting
confidence: 47%
“…An animal model incorporating an adenoviral vector system demonstrated that neuroinflammation is a potential mechanism underlying dSMA-V phenotypes (Seo et al 2014c). In previous studies, ATF3 activation by injurious stimuli was associated with deterioration of motor neurons (Tsujino et al 2000;Hai & Hartman 2001;Vlug et al 2005;de Waard et al 2010) and with cell death programs (Hai & Hartman 2001;Nakagomi et al 2003;Raivich et al 2004).…”
Section: Adenoviral Vector-mediated Animal Models For Motor Impairmentmentioning
confidence: 95%
See 3 more Smart Citations